Functionalized Carbon Nanotubes with Gold Nanoparticles to Fabricate a Sensor for Hydrogen Peroxide Determination - Halimeh Rajabzade; Parandis Daneshgar; Elham Tazikeh; Ramin Zafar Mehrabian (E-Journal of Chemistry)
A highly sensitive electrode was prepared based on gold nanoparticles/nanotubes/ionic liquid for measurement of Hydrogen peroxide. Gold nanoparticles of 20–25 nm were synthesized on a nanotube carbon paste electrode by cyclic voltammetry technique while the coverage was controlled by applied potential and time. The gold nanoparticles were modified to form a monolayer on CNT, followed by decoration with ionic liquid for determination of hydrogen peroxide. The experimental conditions, applied potential and pH, for hydrogen peroxide monitoring were optimized, and hydrogen peroxide was determined amperometrically at 0.3 V vs. SCE at pH 7.0. Electrocatalytic effects of gold deposited CNT were observed with respect to unmodified one. The sensitivity obtained was 5 times higher for modified one. The presence of Au particles in the matrix of CNTs provides an environment for the enhanced electrocatalytic activities. The sensor has a high sensitivity, quickly response to H2O2 and good stability. The synergistic influence of MWNT, Au particles and IL contributes to the excellent performance for the sensor. The sensor responds to H2O2 in the linear range from 0.02 µM to 0.3 mM. The detection limit was down to 0.4 µM when the signal to noise ratio is 3.